A Custom-made nasal prosthesis rehabilitation post total rhinectomy - Wina Meiana Wijaya; Fransiscus Wihan Pradana; Intan Ruspita (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Sinonasal carcinoma (SNC) is a rare but aggressive malignancy often diagnosed at an advanced stage. Total rhinectomy, though potentially life-saving, results in significant functional and psychosocial impairments. This case highlights the use of a custom-made room temperature vulcanizing (RTV) silicone nasal prosthesis as a non-invasive rehabilitation option post-rhinectomy. A 50-year-old male presented with persistent nasal discharge and epistaxis. Imaging and biopsy confirmed high-grade non-intestinal type sinonasal adenocarcinoma, staged as T4aN0M0 (Stage IVA). The patient underwent total rhinectomy followed by radiotherapy. After sufficient healing, maxillofacial prosthetic rehabilitation was initiated. The nasal prosthesis was fabricated using RTV silicone and retained with eyeglasses. At one-month follow-up, the patient reported excellent prosthetic function, aesthetic satisfaction, and improved self-esteem, with no complications. This case demonstrates that custom-made nasal prostheses using RTV silicone can effectively restore aesthetics and function following total rhinectomy. It further underscores the importance of a multidisciplinary approach and individualized treatment planning in optimizing patient outcomes.